Dispersive thinking process to construct self-regulated learning ability in a "conceptual embodied" world - Hidajat, Flavia Aurelia (Desimal: Jurnal Matematika, 2021)
Dispersive thinking is a process of expanding knowledge through reflective thinking, followed by creative thinking and producing various alternative solutions / answers that are unique, new, and appropriate. This research aims to describe students' dispersive thinking processes in constructing their self-regulated learning in a "Conceptual Embodied" world. Data collection methods are non-routine tests (problems) related to flat shapes, interviews, and think out loud. The results showed that students' dispersive thinking processes in constructing self-regulated learning in the "Conceptual Embodied" world consisted of the following stages: experiencing confusion (presence of experience), identifying problems, synthesizing ideas, building ideas, implementing ideas. The researcher recommends that the construction of a flat concept in the "Conceptual Embodied" world should focus on the development of the students' dispersive thinking stages.